NATURE AND FORMS OF REALIZATION OF LEGAL LIABILITY - Baikovs, Aleksandrs (Administrative and Criminal Justice, 2019)
The article focuses on the research of one of the fundamental institutions of law – legal liability, the role and importance of which in the current period of formation of the rule of law in Latvia is constantly increasing. However, many issues of legal liability are still under discussion. In recent years the problem of liability mainly out of legal problem, turned into a problem of interdisciplinary nature. The generic notion, in relation to legal liability, is social responsibility. The evolution of views on the nature of legal liability has resulted in the emergence of the concept of positive legal liability. The initial methodological premise of the research of legal liability is to address to the issue of social responsibility, since the general characteristics and forms of realization inherent in social responsibility, inevitably find their expression both: in legal responsibility and its individual types. Traditionally, legal liability is limited by its interpretation as liability for the past, i.e. negative liability. At the same time, attention is drawn to the diversity of views and interpretations of supporters of this approach. However, in recent decades, there has been a growing body of research on positive (prospective) responsibility, whose proponents are also diverse. Moreover, in science it is suggested, that responsibility can be extremely positive, along with which, the protection of violated subjective rights and interests protected by law, is provided by measures of state coercion. http://dx.doi.org/10.17770/acj.v4i85.4015 Legal liability is considered in the article as an holistic phenomenon, dialectical unity of responsibility for past actions (retrospective responsibility) and responsibility for present and future behavior (positive, prospective responsibility), which develops and is implemented in a voluntary or compulsory form in regulatory legal relations. Legal liability is characterized by a number of specific features. Among them: (1) legal liability is based on legal norms, that give it certainty and general compulsion; (2) state guarantee; (3) provision of state coercion or persuasion; (4) legal liability as a necessary consequence has the approval or conviction, encouragement or punishment; (5) legal liability is implemented in the procedural form, provided for by law; (6) essentially, legal liability is a uniform, but it is exercised in two different forms. The theories and concepts of legal liability, presented in the scientific literature were critically analyzed in the article and on this basis its concept is being formulated, the specific features inherent in legal liability are being identified, its unity and the presence of various forms of implementation are being alleged.